Advancement of Gate Oxides from SiO2 to High-k Dielectrics in Microprocessor and Memory. Issue 1 (1st May 2022) - Sharma, U.; Kumar, G.; Mishra, S.; Thomas, R.
Abstract: Silicon and its native oxides (SiO2 ) have led the continuous development in the integrated circuits for decades. The excellent insulating properties of SiO2 and silicon/SiO2 interface quality were used as capacitor dielectrics in random-access memories (RAM's) and transistor gate dielectrics in complementary metal-oxide semiconductor (CMOS's), respectively, for the memory and logic devices. These are the core components and act as the heart of the semiconductor industry. However, reducing the thickness of SiO2 to increase the capacitance at a reduced lateral size resulted into high leakage current and large power consumption in the aforementioned high-density semiconductor devices. To overcome this concern, high-permittivity materials were considered in replacing the SiO2 to achieve high capacitance at a higher thickness. Numerous materials ranging from Al2 O3 ( k 9) to perovskites ( k 10 2 -10 4 ) are being actively investigated but Hafnium based compound high- k dielectric/metal gate ( k 10-15) captivate great attention and used for logic and memory devices. However, finding a real high- k material ( k 25-40) with silicon is a major challenge by itself as it requires an ideal interface with minimum defects. Therefore, with this article, we review the efforts in replacing SiO2 with higher- k dielectrics over the years to match the performance of processor from generation to generation.